Toward a Measurable Islamic Soft Skills Model: Integrating Spiritual Values into Competency-Based Education - Aries Musnandar; Sutrisno; A. Fahrur Rozi; Kartika Ratnasari; Diaya Uddeen Deab Mahmoud Alzitawi (Al-Mudarris, 2026)
The growing emphasis on soft skills in 21st-century education highlights the need for frameworks that integrate ethical and spiritual dimensions into competency development. However, existing soft skills models remain largely secular and provide limited operational mechanisms for translating religious values into measurable learning outcomes. This study addresses this gap by developing an Islamic soft skills framework grounded in Qur’anic principles and Islamic virtue ethics. Using qualitative content analysis and an integrative literature review, the study synthesizes classical Islamic educational thought with contemporary competency-based education frameworks. The analysis focuses on three core Islamic virtues ṣabr (patience), shukr (gratitude), and ikhlāṣ (sincerity) as foundational dimensions of behavioral competency development. The findings propose a structured framework based on Tawḥīd (spiritual orientation), Khilāfah (ethical responsibility), and Muru’ah (moral excellence), which are operationalized into observable behavioral indicators and assessment-oriented learning outcomes. The framework provides a conceptual bridge between Islamic ethical philosophy and competency-based educational practice. This study contributes theoretically by offering a measurable Islamic soft skills model that integrates spiritual values with competency-based indicators, while also providing practical implications for curriculum development, character education, and future empirical validation within Islamic educational settings.